TDP-43 is associated with a reduced likelihood of rendering a clinical diagnosis of dementia with Lewy bodies in autopsy-confirmed cases of transitional/diffuse Lewy body disease - Buciuc, Marina (J Neurol, 2020)
BACKGROUND: Trans-active response DNA-binding protein of 43kDa (TDP-43) can be detected in up to 63% of autopsy confirmed Lewy body disease (LBD) cases. It is unclear whether TDP-43 is associated with a decreased likelihood of a clinical diagnosis of probable dementia with Lewy bodies (pDLB) during life. METHODS: In an autopsy cohort of 395 cognitively impaired patients from the Mayo Clinic Alzheimer’s Disease Research Center, we determined the presence of TDP-43 in the hippocampus (hTDP-43(+)) and examined associations between hTDP-43 and an antemortem pDLB clinical diagnosis with multiple regression analyses. For this study, given our specific question, we only counted transitional and diffuse Lewy body disease as LBD positive (LBD+). RESULTS: One-hundred forty-five cases (37%) were hTDP-43(+) and 156 (39%) were LBD+; co-pathology was noted in 63 (16%) cases. Patients with pDLB-LBD+ were more likely to be older, hTDP-43(+) and have high Braak neurofibrillary tangle (NFT) status compared to the pDLB+LBD+ patients. After accounting for older age at death and high Braak NFT status, hTDP-43(+) status was associated with the absence of a clinical diagnosis of pDLB despite LBD+ status (p<0.05). CONCLUSION: The absence of a diagnosis of pDLB during life in patients with LBD is associated with older age, high Braak NFT stage and hTDP-43, each feature contributing independently to a lower likelihood of a clinical diagnosis of pDLB during life.